Blended Learning as an Alternative Learning in Elementary Schools - Hendra Prasetia Prasetia (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2023)
The problem of learning during the Covid-19 pandemic was that it could not be held face-to-face so that blended learning was an alternative learning solution. This problem occurs in various regions. Learning in the conditions of the Covid-19 pandemic is difficult to find a solution, because it is caused by various problems from students, teachers and schools. So that learning outcomes and student motivation do not decrease, Blended Learning is used to overcome them. The writing of this article uses the systematic literature review method in reviewing it. From the findings of research results in various journals by writing down keywords totaling 104,000 articles, then identified based on citations and years, so that there are 16,900 articles. Then verification of the articles based on topic suitability was carried out into 10 articles and synthesis analysis was carried out on the existing articles into 5 articles, and the final stage was to describe the findings of the articles to draw conclusions. Various findings in research show that blended learning motivates and improves student learning outcomes. Blended-Learning is seen as providing a variety of variations, completeness and learning flexibility in the use of place, time, and access to lessons.